2010
DOI: 10.2220/biomedres.31.329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a vitamin D analog, alfacalcidol, on bone and skeletal muscle in glucocorticoid-treated rats

Abstract: Glucocorticoids cause secondary osteoporosis and myopathy. The efficacy of vitamin D on osteoporotic fractures is thought to be through direct effects on bone and indirect effects on muscles that help to prevent falls. However, effects of vitamin D on muscles under glucocorticoid treatment remain unclear. Six-month-old female Wistar rats were randomized to four groups: vehicletreated controls; a prednisolone (PSL)-administered group (PSL group); an alfacalcidol-administered group (D group); and a group adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Our previous studies have shown that alfacalcidol increased muscle strength, but did not affect muscle fatigue, in ovariectomized rats [15], whereas it preserved both BMD and muscle strength and volume and prevented muscle fatigue in glucocorticoid-treated rats [16]. Similarly, in the present study, eldecalcitol increased muscle strength and volume in glucocorticoid-treated rats, but did not affect muscle fatigue.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Our previous studies have shown that alfacalcidol increased muscle strength, but did not affect muscle fatigue, in ovariectomized rats [15], whereas it preserved both BMD and muscle strength and volume and prevented muscle fatigue in glucocorticoid-treated rats [16]. Similarly, in the present study, eldecalcitol increased muscle strength and volume in glucocorticoid-treated rats, but did not affect muscle fatigue.…”
Section: Discussionsupporting
confidence: 76%
“…Prednisolone (PSL) (Predonine; Shionogi Pharmaceutical, Osaka, Japan) was dissolved in 0.9 % saline, and 10 mg/kg/day was injected subcutaneously every day for 2 or 4 weeks. This dose was determined previously to cause steroid myopathy [16]. Eldecalcitol (Chugai Pharmaceutical, Tokyo, Japan) at a dose of 0.05 µg/kg/day dissolved in medium-chain triglyceride (MCT) or MCT alone was administered orally every day for 2 or 4 weeks.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The results (Table 1) show that of 141 searches performed in PubMed only 16 yielded results totalling 35 papers. Of these, seven related to the periodontal ligament (Albair et al, 1982;Bragger et al, 1990;Fernyhough and Page, 1983;Isidor et al, 1985;Karring et al, 1985;Luder and Zappa, 1998;Nishimura et al, 1989), and four related to experiments in non-human animals (Harris et al, 2002;Hashimoto et al, 2007;Miyakoshi et al, 2010;Suliman et al, 1997). Of the remaining papers, seven focus on one specific condition: calcific tendinitis (Cahir and Saifuddin, 2005;Chadwick, 1989;Dürr et al, 1997;El-Essawy and Vanhoenacker, 2012;Fritz et al, 1994;Hayes et al, 1987a;Ikegawa, 1996).…”
Section: Resultsmentioning
confidence: 99%